TRANSPORTASI SISTEM TERTUTUP BENIH IKAN NILA (Oreochromis niloticus) MENGGUNAKAN MINYAK CENGKEH (Eugenia aromatic) DENGAN DOSIS BERBEDA - Verdian, Aldi Huda; Indariyanti, Nur; Antaqo, Dwi Suryati (Politeknik Negeri Lampung, 2023)
Tilapia (Oreochromis niloticus) seeds is one of the fishery products that is in great demand by the public. National tilapia production increases every year. Transporting seeds is what determines success in maintaining survival during the transportation process. However, the transportation process can cause the fish to become stressed and vulnerable to death. This problem can be prevented by stunning the fish first. Anesthesia is carried out with the aim of extending transportation time by suppressing the fish's metabolic activity. The organic ingredient that can be used as an anesthetic is clove oil. Clove oil contains eugenol which can be used as an anesthetic for fish. The aim of this activity is to see the effectiveness of clove oil as an anesthetic agent in closed system transportation of tilapia seeds. The method used was 135 animals/treatment using 3 treatments and 1 control. Doses K (0.0%), A (0.25%), B (0.30%), and C (0.35%) with 3 repetitions. The experimental results showed that the highest survival value was in A 0.25% (2.5ml/l) with 90%, while the lowest survival value was in the C treatment with a survival value of 57.50%. The longest fish fainting time was in the C treatment with the fish fainting time being 120.2 minutes, while in B the fish fainting time was 107.7 minutes. The best effective dose used as an anesthetic in the process of transporting tilapia fry measuring 5-7 cm is 0.25% (2.5ml/l).